Mediating effects of mental and physical health on the association between chronic disease conditions and colorectal cancer screening utilization among breast cancer survivors - Meng-Han Tsai; Jacqueline B. Vo; Justin X. Moore; Cody Ramin; Avirup Guha; Yanbin Dong (PLoS ONE, 2025)
Purpose Breast cancer survivors have an increased risk of colorectal cancer (CRC) and those with chronic diseases are more likely to experience poor mental and physical health. For this study, we examined the mediating effects of mental and physical health on the association between chronic disease conditions and guideline-concordant colorectal cancer (CRC) screening among breast cancer survivors. Methods We included 1,885 breast cancer survivors aged 45–75 years who were eligible for CRC screening in 2016, 2018, and 2020 Behavioral Risk Factor Surveillance System. The exposure was chronic diseases defined as prevalent diabetes, coronary heart disease/myocardial infarction, stroke, chronic obstructive pulmonary disease, emphysema/chronic bronchitis, arthritis, depressive disorders, or kidney diseases. The outcome was receipt of guideline-concordant CRC screening. Mediators were defined as self-reported frequent poor mental/physical health in the past 30 days (14–30 vs. 0–13 days). Multivariable logistic regression models were adjusted for sociodemographic and cancer-related factors. We used the methods proposed by Valeri & VanderWeele for the mediation analyses. Results Breast cancer survivors with chronic diseases were 1.7-fold more likely to have CRC screening compared to those without any chronic diseases (OR, 1.68; 95% CI, 1.27–2.21). In mediation analysis, we found that frequent poor mental health mediated the association between chronic disease conditions and CRC screening utilization (−4.4% mediated; p-value = 0.035). We also observed a reduction through frequent poor physical health by 10.5% (p-value = 0.008). Conclusions Frequent poor mental and physical health negatively mediated the association between the presence of chronic diseases and CRC screening utilization with a higher estimate for those with poor physical health. Effective implementation of integrated follow-up care is needed among breast cancer survivors to address chronic disease management and prioritize mental and physical health so that all patients receive guideline concordant CRC screening recommendations.